2023
DOI: 10.1111/bdi.13351
|View full text |Cite
|
Sign up to set email alerts
|

Emerging psychopathology and clinical staging in adolescent offspring of parents with bipolar disorder or schizophrenia—A longitudinal study

Abstract: ObjectivesOffspring of parents with bipolar disorder (BDo) and schizophrenia (SZo) are at increased risk for these disorders and general psychopathology. Little is known about their (dis)similarities in risk and developmental trajectories during adolescence. A clinical staging approach may help define the developmental course of illness.MethodsThe Dutch Bipolar and Schizophrenia Offspring Study is a unique cross‐disorder and prospective cohort study, established in 2010. In total, 208 offspring (58 SZo, 94 BDo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…It is important to note that most of the offspring in this study have not yet reached the typical age of onset at which the intergenerational homotypic continuity of psychopathology from parent to offspring can be observed ( 11 , 12 , 68 ). While (sub)clinical symptoms in the psychotic and several other domains are present in both high-familial-risk groups, the number of offspring diagnosed with a bipolar or psychotic disorder in this cohort is very low ( 69 ). Because more of them are likely to develop psychosis or bipolar disorder ( 4 , 5 , 6 ), following these offspring further into adulthood is imperative because it will allow us to determine how connectome development pertains to risk of or resilience against later severe mood or psychotic disorder.…”
Section: Discussionmentioning
confidence: 85%
“…It is important to note that most of the offspring in this study have not yet reached the typical age of onset at which the intergenerational homotypic continuity of psychopathology from parent to offspring can be observed ( 11 , 12 , 68 ). While (sub)clinical symptoms in the psychotic and several other domains are present in both high-familial-risk groups, the number of offspring diagnosed with a bipolar or psychotic disorder in this cohort is very low ( 69 ). Because more of them are likely to develop psychosis or bipolar disorder ( 4 , 5 , 6 ), following these offspring further into adulthood is imperative because it will allow us to determine how connectome development pertains to risk of or resilience against later severe mood or psychotic disorder.…”
Section: Discussionmentioning
confidence: 85%
“…6 Previous longitudinal investigations in the offspring of parents with bipolar disorder (O-BD) suggested the emergence of various non-mood disorders prior to the onset of bipolar disorder, including sleep and anxiety disorders in late childhood, adjustment disorders and dysthymia in early adolescence, and major depression in late adolescence. [7][8][9] Recently, there has been a growing consensus that sleep/circadian rhythm dysfunction may be one of the key prodromes as well as core manifestations of bipolar disorder. Existing evidence indicated that sleep alterations may serve as precursors of the initiation of bipolar disorder, and dynamic changes in sleep patterns accounted for one-third of the predictable explained variance in the multivariate psychiatric symptom outcomes.…”
mentioning
confidence: 99%